Computer modeling in tailoring of funtionally graded material and design optimization of femoral component in total knee replacement to reduce aseptic loosening - Bahraminasab, Marjan (2014)
Aseptic loosening is the main reason for failure/revision of Total Knee Replacements (TKR), which occurs for all TKR components including femoral, tibial and patellar components. It is particularly problematic for femoral component because its failure can be associated with different causes. The judicious considerations of femoral component materials and design may provide an immune response to aseptic loosening problem by minimizing the occurrence of leading causes. Literature review showed the need for more sophisticated multi-functional materials to be developed in order to match thebiological and mechanical complexity of the prosthetic femur. To reduce aseptic loosening problem a new multi-functional material, a functionally graded biomaterial (FGBM) composed of alumina and titanium, was introduced for femoral component. FGBM consists of two or more biocompatible constituents, whose mechanical properties vary with positions and can be designed for specific application. The potential advantages of applying FGBM were explained by reducing the leading causes of failure; wear, micro-motion and stress shielding effect. The primary proposed design of FGBM was analyzed using finite element to investigate the stress level in the distal femur and to find the influence of the suggested material on stress shielding effect. The results obtained were compared to using a standard femoral component material both with and without cement fixation, which showed the superiority of the proposed FGBM without cement fixation. In order to have more precise material design leading to optimal function, a multiobjective design optimization for an FGBM femoral component was carried out using finite element analysis (FEA) and response surface methodology (RSM). Three performance outputs including stress shielding effect, micro-motion and wear index were optimized with respect to three FGBM design variables. Overall, the optimal FGBM showed better results; on average 3.8%, 13.6%, and 0.6% improvements were found in the mean stress of the femur, mean micro-motion of the interface and wear index of insert, respectively compared with the use of standard Co-Cr alloy. One of the geometrical features that play an important role in the effectiveness of primary and revision knee prostheses is the peg or stem. The design of the location pegs in the femoral component of the knee prosthesis is seen to have a critical effect on stress shielding. Therefore, different combinations of location peg geometries and material designs were assessed using FEA in conjunction with design of experiments. A multiobjective optimization was carried out to find the optimal geometries of peg for the femoral component and based on the results obtained a set of candidate designs was generated and a multi-criteria decision making approach used for final ranking. It was found that a FGBM femoral component with 60% porous Ti conical peg is the most suitable design. The selected design which was based on integration of material and geometry design, showed more than 10% improvement, on average, in stress shielding effect.